THE NEW TRAINING TECHNOLOGIES IN GOLF - čoh, Milan (Scientific Journal Management in Sports, 2014)
Golf is an extremely complex game which depends on a number of interconnected factors. One of the most important elements is undoubtedly the golf swing technique. High perfor- mance of the golf swing technique is generated by: the level of motor abilities, high degree of movement control, the level of movement structure stabilisation, morphological characteris- tics, inter- and intro-muscular co-ordination, motivation, and concentration. The golf swing technique was investigated using the biomechanical analysis method. Kinematic parameters were registered using two synchronised high-speed cameras at a frequency of 2.000 Hz. The sample of subjects consisted of three professional golf players. The study results showed a rela- tively high variability of the swing technique. The maximum velocity of the ball after a wood swing ranged from 233 to 227 km/h. The velocity of the ball after an iron swing was lower by 100 km/h on average. The elevation angle of the ball ranged from 11.7 to 15.3 degrees. In the final phase of the golf swing, i.e. downswing, the trunk rotators play the key role.